PENERAPAN MODEL PROJECT BASED LEARNING (PjBL) UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS XII DI SMA N 4 SEMARANG - Agustin Wulandari; Andari Puji Astuti; Yuyun Eka Wardani (LitbangMu Jawa Tengah and Teacher Professional Education UNIMUS, 2025)
This study was motivated by the low motivation and learning achievement of students in class XII-3 SMA N 4 Semarang known from the observation results. The research objectives are to (1) Know the increase in learning motivation of XII grade students in Electrochemistry material using the Project Based Learning (PjBL) model, (2) Know the increase in learning achievement of XII grade students in Electrochemistry material using the Project Based Learning (PjBL) model. This research is a type of classroom action research with a model developed by Kemmis and Mc.Taggart. Data analysis techniques using quantitative and qualitative descriptive analysis. The application of the PjBL learning model can increase student learning motivation. This is indicated by the results of questionnaire data in Cycle I obtained 80.77% and Cycle II amounted to 90% which shows an increase in learning motivation by 9.23%. The application of the PjBL learning model can also improve student learning achievement as shown by the average pretest and post test scores in Cycle I of 60.31 and 87.53 while Cycle II was 83.72 and 97.78. This shows that there is an increase in student learning achievement. Student learning achievement has achieved success indicated by the number of students who have achieved KKTP as much as 81% in Cycle I and Cycle II as much as 100%.